The Effects of Resveratrol and Pioglitazone Treatment on Serum Resistin and Apelin Levels and Histochemical Parameters in the Metabolic Syndrome Rat Model: Animal Experiment - Gürsu, Onur; Altaş, Sevgi; Dönder, Emir; Gürsu, Mehmet Ferit; Karaman, Muhammed Emre (Turkiye Klinikleri, 2023)
Objecvtive: The current research was aimed to determine the serum resistin and apelin levels in rats with metabolic syndrome and to examine the impact of resveratrol and pioglitazone intervention on serum resistin, apelin levels and metabolic parameters. Material and Methods: Fourty male Wistar albino rats were divided into 4 groups. Group 1 [n=10, control group; without (metabolic syndrome “MetS”)]; Group 2 (n=10, MetS group without treatment); Group 3 (n=10, MetS and treatment with resveratrol); Group 4 (n=10, MetS and treatment with pioglitazone). The rats were decapitated and resistin, apelin and biochemical parameters were studied in blood sam-ples. Results: Apelin levels did not decreased in MetS+pioglitazone treatment group. Resistin level significantly decreased in treatment groups. Myxoid degeneration and edema in aortic vessel wall were less severe in MetS+resveratrol group. Periportal sinusoidal enlargement, congestion and lymphocyte infiltration in rat liver tissue with metabolic syndrome were absent in the group treated with resveratrol, and re-gressed in the group treated with pioglitazone treatment. Conclusion: Resistin and apelin concentrations have found to be increased in MetS and associated with insulin re-sistance. Although pioglitazone and resveratrol treat-ment decreased resistin levels, it was ineffective on apelin levels. Although pioglitazone treatment pro-vided improvement in histopathological changes, resveratrol treatment had more benefits on histopathological changes. In the treatment of metabolic syndrome, resveratrol may be useful in support therapy. This study is the first study which shows that pioglitazone does not effects the apelin levels in metabolic syndrome treatment. © 2023 by Türkiye Klinikleri.
Rat Metabolik Sendrom Modelinde Resveratrol ve Pioglitazon Tedavisinin Serum Resistin ve Apelin Düzeyleri ile Histokimyasal Parametreler Üzerine Etkileri: Hayvan Deneyi
Keywords: apelin; Metabolic syndrome; pioglitazone; resistin; resveratrol